Detection of Trichuris eggs in feces and soil from giraffe (Giraffa camelopardalis) and other hoofstock enclosures under human care in the USA. (August 2021) - Shusterman, Lauren; Marsh, Antoinette E.; Joyner, Priscilla H.; Habing, Greg
Abstract: Trichuris spp. are nematode parasites infecting wild ruminants in zoological institutions worldwide. These helminths cause significant morbidity in giraffe ( Giraffa camelopardalis ) and other hoofstock located in zoological institutions throughout the United States. Historically, studies and institutions have used a variety of nematode detection methods with various flotation solutions. Optimization of Trichuris egg detection is necessary for monitoring collections. Fecal and soil optimized protocols were generated in this study using samples containing Trichuris eggs from multiple semi free-ranging zoological institutions. First, Sheather's sugar (specific gravity (SG) 1.27), sucrose (SG 1.40), magnesium sulfate (SG 1.26), and zinc sulfate (SG 1.18) were compared as flotation solutions by quantitative eggs per gram using a modified Stoll method. Then a soil recovery method was optimized comparing Tween 20, sodium hydroxide, Dawn™ (Procter and Gamble) detergent, and sodium chloride as liberating solutions to free eggs from the soil. We found that Sheather's sugar and sucrose solutions were the most effective for Trichuris egg detection, and either sodium hydroxide or sodium chloride liberated eggs from soil. Graphical abstract: Trichuris  egg seen in fecal flotation of giraffe feces. Image 1 Highlights: Optimization of giraffe Trichuris egg detection. Soil Trichuris recovery methods analysis. Multi-institutional giraffe Trichuris evaluation.